(untitled) (Annals of Medical Research, 2021)
Aim: Genetic variations contribute differences in defensive behaviors among individuals. However, the exact role of heritability in the etiology of defensive behaviors like dental anxiety is not elucidated clearly. Twin studies provide an excellent source to investigate the relative contribution of genetics and environment in various phenotypic traits or disorders. Therefore, the aim of this study is to explore the relative contribution of genetics on dental anxiety on Turkish twins by using the classical twin method. Material and Methods: Corah’s Dental Anxiety Scale used for the anxiety measurement of 70 pairs of Turkish twins. Decayed, Missing, Filled-Teeth (DMF-T) index was calculated according to the number of decayed, missing and filled teeth after clinical and radiological examinations.Results: No significant differences and correlations found within the dental anxiety scores of Monozygotic (MZ) and Dizygotic (DZ) twin-pairs. Significant positive correlation for DMF-T scores was found within the MZ and DZ twin-pairs.Conclusion: Based on the data obtained from our study, it can be concluded that environmental factor appears to have a more dominant effect on dental anxiety and the high correlation regarding DMF-T among MZ twin pairs indirectly shows the genetic effect on dental caries.